Involvement of 5-hydroxytryptamine and prostaglandin E2 in the intestinal secretory action of Escherichia coli heat-stable enterotoxin B. - Harville, B A (1995)
The intestinal secretory action of Escherichia coli heat-stable enterotoxin B (STb) is poorly defined. Previous work indicates that STb causes loss of intestinal fluid and electrolytes by a mechanism independent of elevated levels of cyclic nucleotides, the hallmark of other E. coli cytotonic enterotoxins. In the work described in this report, we observed that treatment of ligated rat intestinal loops with purified STb of E. coli resulted in a dose-dependent rise in intestinal secretion concomitant with dose-related increases in levels of serotonin (5-hydroxytryptamine [5-HT]) and prostaglandin E2 (PGE2). Treatment of rats with the 5-HT2 receptor antagonist ketanserin prior to STb challenge resulted in significant (P < 0.05) reduction in intestinal secretion. Blockage of 5-HT2 receptors with ketanserin also reduced (P < 0.05) the level of PGE2 observed following STb treatment, indicating that at least a portion of the PGE2 was formed in response to 5-HT2 receptor stimulation. In a similar fashion, indomethacin, an inhibitor of cyclooxygenase activity, significantly reduced the level of secretion (P < 0.05) observed following STb treatment yet had no effect on 5-HT levels. Treatment of rats with both ketanserin and indomethacin further reduced STb-mediated secretion to a level not attained by either drug alone. Taken together, our data suggest that secretion due to STb involves both 5-HT and PGE2 as intestinal secretagogues. Furthermore, PGE2 formation appears to arise through both 5-HT-dependent and 5-HT-independent pathways.